An insight into the different responses to salt stress in growth characteristics of two legume species during seedling growth - Mi, Jia; Ren, Xinyue; Shi, Jing; Wang, Fei; Wang, Qianju; Pang, Haiyan; Kang, Lifang; Wang, Changhui (Frontiers in Plant Science, 2024)
Legumes play a crucial role in the restoration and utilization of salinized grassland. To explore the physiological response mechanism of Astragalus membranaceus and Medicago sativa seedlings to salt stress, salt stress culture experiments with five NaCl concentration treatments (0 mmol/L, 50 mmol/L, 100 mmol/L, 200 mmol/L, and 300 mmol/L) were conducted on these two legume seedlings. Morphological characteristics, physiological features, biomass, and the protective enzyme system were measured for both seedlings. Correlation analysis, principal component analysis (PCA), and membership function analysis (MFA) were conducted for each index. Structural equation modeling (SEM) was employed to analyze the salt stress pathways of plants. The results indicated that number of primary branches (PBN), ascorbate peroxidase (APX) activity in stems and leaves, catalase (CAT) activity in roots, etc. were identified as the primary indicators for evaluating the salt tolerance of A. membranaceus during its seedling growth period. And CAT and peroxidase (POD) activity in roots, POD and superoxide dismutase (SOD) activity in stems and leaves, etc. were identified as the primary indicators for evaluating the salt tolerance of M. sativa during its growth period. Plant morphological characteristics, physiological indexes, and underground biomass (UGB) were directly affected by salinity, while physiological indexes indirectly affected the degree of leaf succulence (LSD). Regarding the response of the protective enzyme system to salt stress, the activity of SOD, POD, and APX decreased in A. membranaceus, while the activity of APX and CAT increased in M. sativa. Our findings suggest that salt stress directly affects the growth strategies of legumes. Furthermore, the response of the protective enzyme system and potential cell membrane damage to salinity were very different in the two legumes.